2017
DOI: 10.21859/jech.4.2.28
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Anxiety, Stress, and Depression with Spiritual Health in Patients with Acute Coronary Artery Disease

Abstract: Background and Objective: Anxiety, stress, and depression can cause chest pain. On the other hand, spiritual health plays an important role in acceptance of disease. In this study, we attempted to investigate the relationship of stress, anxiety, and depression with spiritual health in patients with acute coronary syndrome. Materials and Methods:This descriptive-analytical study was performed on 294 patients with acute coronary syndrome during 10 months in teaching hospitals affiliated to Qom University of Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies have shown that spiritual health correlates with a shorter hospital stay, lower anxiety, and hopelessness, and overall health improvement (8)(9)(10). The study performed by Ghanbari Afra et al (11) revealed a relationship between anxiety, stress, and depression in patients with acute coronary syndrome. They showed that those who had higher spiritual health experienced less anxiety, stress, and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that spiritual health correlates with a shorter hospital stay, lower anxiety, and hopelessness, and overall health improvement (8)(9)(10). The study performed by Ghanbari Afra et al (11) revealed a relationship between anxiety, stress, and depression in patients with acute coronary syndrome. They showed that those who had higher spiritual health experienced less anxiety, stress, and depression.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Clinical and experimental research has demonstrated that stress is associated with increased psychiatric disorders such as depression and anxiety. [10][11][12] The most debilitating complication of stress is depression, which affects the body's overall function, including the cardiovascular, 13,14 gastrointestinal, 15 immune, 16 and brain structure and function. 9,17 In addition, depression is a profound public health concern with various physical ailments, reduced social functioning, a significant cause of disability, and increased mortality.…”
Section: Introductionmentioning
confidence: 99%